Zwyczaj palenia tytoniu w słownictwie i frazeologii języka polskiego - Piela, Agnieszka (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
Polish phraseology contains a large number of lexical units reflecting old customs of Polish people. Among them, one can find those which originate either from the tobacco smoking custom or the habit of taking snuff. The article deals with the lexis and phraseology from the so-called “tobacco circle”. The semantic field of the names under examination is treated in a broader scope; thus it contains not only lexemes: cigar, pipe, cigarette, snuff, tobacco, but also the names of accessories and people connected with a tobacco industry such as: cigar-holder, pipe maker, cigarette manufacturer, cigarette-case, snuff-box, and the verbs describing smoking tobacco actions such as puff, drag, toke, fume, smoke.